Nitro‐Substituted Bishomocubanes: Synthesis, Characterization, and Application as Energetic Materials. Issue 12 (14th October 2014) - Lal, Sohan; Rajkumar, Sundaram; Tare, Amit; Reshmi, Sasidharakurup; Chowdhury, Arindrajit; Namboothiri, Irishi N. N.
Abstract Several high‐energy‐density strained polycyclic compounds nitromethyl‐l, 3‐bishomocubane (NMBHC), nitromethylene‐1, 3‐bishomocubane (NMyBHC), and bis(nitromethyl)‐1, 3‐bishomocubane (DNTMBHC), which were synthesized for the first time from bishomocubanone, hold potential for application as standalone fuels in liquid bipropellant systems or as additives in liquid and solid propellant formulations. DFT analysis at the B3LYP/6‐31G(d) level of theory was employed to optimize the geometries of the compounds and to determine their densities, heats of formation, and various thermodynamic properties. The density specific impulse, determined by using equilibrium thermodynamics, demonstrated an improvement of 75 s for NMBHC and NMyBHC over standard hydrocarbons. The specific impulse with ammonium perchlorate showed an improvement of 25–30 s over hydroxy‐terminated polybutadiene. Thermogravimetric analysis revealed that NMBHC, NMyBHC, and DNTMBHC evaporated readily with activation energies of 58.8, 69.2, and 74.5 kJ mol−1, respectively.